Application of magneto-rheological damper for car suspension control - Rashid, M.M.; Hussain, Mohd Azlan; Rahim, N. Abd (Journal of Applied Sciences, 2006)
The MR damper is a control device that consists of a hydraulic cylinder filled with magnetically polarizable particles suspended in a liquid. MR dampers dissipate vibration by absorbing energy. Magnetorheological (MR) fluids dampers are very effective to control vibration, which use MR fluids to produce controllable damping force and provide both the reliability of passive systems and the facility of active control systems with small power supply. Due to their mechanical simplicity, high dynamic range, low power requirements, large force capacity and robustness, offer an attractive means of vibration protection. The objective of this study are understanding the characteristics of the MR damper to provide effective damping for the purpose of suspension isolation or suppression car body. In this study, fuzzy logic controller is used to control semiactive car suspension system.